The Theory of Storage and Price Dynamics of Agricultural Commodity Futures: the Case of Corn and Wheat - Benavides Perales, Guillermo (Universidad Autónoma de Nuevo León, 2010)
Using a restricted version of the BEKK model it is tested an implication of the theory of storage that supply-and-demand fundamentals affect the price dynamics of agricultural commodities. The commodities under analysis are corn and wheat. An interest-storage-adjusted-spread was used as a proxy variable for supply-and-demand fundamentals to test the aforementioned implication for both commodities. It is also tested the Samuelson hypothesis that spot prices have higher volatility than futures prices. It is found that the interest-storage-adjusted-spread has had a statistically significant positive influence on the spot and futures returns for both commodities. Likewise, the results also show that spot price returns have higher volatility compared to futures price returns which is consistent with the Samuelson hypothesis. The results of the aforementioned tests are consistent with both theories and with the existing literature related to commodity futures. JEL Classification: C22, G10, Q14.